A COMPETITIVE STUDY OF CAR SALES IN BUSINESS AND E- BUSINESS - Johar; MGM; Yajid, Mohd Shukri Ab (International Journal of Psychosocial Rehabilitation, 2020)
The research in this study can be considered as both exploratory and descriptive, but mainly explorative. Three case studies have been conducted, where both secondary and primary data were used. The analysis is based on the empirical findings, as well as on the theoretical Frame Work for this study. The conditions for doing business are rapidly changing. Consumptions patterns are different, there are new technologies for distributing and collecting information, and the competition on the market is increasing domestically as well as globally. In order for companies to survive and grow they must find new ways of thinking, which has led to that new approaches has emerged in marketing research. First, Relationship Marketing appeared and now Customer Relationship Management, CRM, is in the center of interest. CRM highlights the importance of using Information Technology in creating, maintaining and enhancing customer relationships. However, there is a need to develop a better understanding of CRM and of how companies can use IT, a CRM system. Thereby, the purpose of this study is to describe CRM and the realization of CRM in companies by using a CRM system. The analysis show that the goal with CRM is to maximize company profits by maximizing the value of interaction with the customers. In order to do this, companies need a business strategy that focuses on the customers and that generates a process-oriented view of the organization. The business processes needs to be supported by a CRM system, comprising CRM functionality that makes it possible to create a single view of the customer as well as of the company. The CRM system also facilitates collection and analysis of customer data, which results in more effective managed customer interactions. The analysis also shows that the stage in the CRM development process affects a company’s view on CRM.